A Monte Carlo analysis of Laser Induced Fluorescence in arterial tissue - Hofmann, G. F.(Gerhard Francois) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.